2016
DOI: 10.1177/1060028016683495
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Hepatitis C Patient Management Program at a University Specialty Pharmacy

Abstract: The UR Specialty Pharmacy was associated with a 93% SVR rate and significantly greater adherence compared with nonintegrated pharmacies. Larger studies are needed to determine if a significant difference in SVR exists between integrated and nonintegrated pharmacies. This study provides a framework for other institutions to justify developing integrated hepatitis C specialty pharmacy services and evaluate their success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…In phase 3 trials, patients with lower adherence to DAAs resulted in suboptimal SVR rates [ 5 , 6 ]. Some studies have indicated that the SVR rates in adherent patients, defined as having the proportion of days covered (PDC) > 80% or 90%, were higher than in non-adherent [ 12 , 15 ]. Enhancement of patients’ adherence to DAAs is a challenge for the achievement of satisfactory therapeutic effect of SVR through IFN-free DAA therapy in real-world clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In phase 3 trials, patients with lower adherence to DAAs resulted in suboptimal SVR rates [ 5 , 6 ]. Some studies have indicated that the SVR rates in adherent patients, defined as having the proportion of days covered (PDC) > 80% or 90%, were higher than in non-adherent [ 12 , 15 ]. Enhancement of patients’ adherence to DAAs is a challenge for the achievement of satisfactory therapeutic effect of SVR through IFN-free DAA therapy in real-world clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…The adherence rate was not influenced by the dosage form (either the combination tablets or the non-combination tablets). Some previous reports have indicated that the SVR12 rate is 88.2–95.3% in real-world settings [ 9 , 12 , 16 18 ], and 84.4–98.1% in phase 2–3 trials [ 15 , 19 21 ]. In this study, the SVR12 rate was 99.6% (Table 2 ), which is relatively higher than in the previous studies [ 9 , 12 , 16 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The University of Rochester HCV integrated management program also has revealed high patient adherence rates and high SVR rates for patients participating in a similar integrated hepatitis clinic model. 25 Taken together, these data demonstrated that an HCVspecialized LSP in collaboration with DAA prescribers may play a key role in the successful completion of DAA therapy.…”
Section: Discussionmentioning
confidence: 70%